Finance and Development, March 2009. (Finance and Development; Finance and Development ;, 2013)
Crisis Stalls Globalization: Reshaping the World Economy" examines the multiple facets of the recession-from the impact on individual economies to the effect on the global payments imbalances that were partially at the root of the crisis-and offers a variety of suggestions for supporting a recovery and averting future crises. Several IMF studies shed light on the depth of the crisis-including a survey of the sharp drop in trade finance, along with quantitative findings about the direct and indirect costs of the financial turbulence-and debate what is to be done from several angles, including the redesign of the regulatory framework and ways to plug large data gaps to prevent future crises and aid in the creation of early warning systems. Opinion pieces discuss the shifting boundaries between the state and markets, the agenda for financial sector reform, and the governance of global financial markets. The issue also includes a historical perspective to see when restructuring the global financial architecture actually succeeds. "People in Economics" profiles Nouriel Roubini; "Back to Basics" looks at what makes a recession; and "Data Spotlight" examines Latin America's debt.